2003
DOI: 10.14214/sf.496
|View full text |Cite
|
Sign up to set email alerts
|

Cost-plus-loss analyses of forest inventory strategies based on kNN-assigned reference sample plot data

Abstract: The usefulness of kNN (k Nearest Neighbour)-assigned reference sample plot data as a basis for forest management planning was studied. Cost-plus-loss analysis was applied, whereby the inventory cost for a specifi c method is added to the expected loss due to non-optimal forestry activities caused by erroneous descriptions of the forest state. Four different strategies for data acquisition were evaluated: 1) kNN imputation of sample plots based on traditional stand record information, 2) imputation based on plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 23 publications
1
59
1
1
Order By: Relevance
“…Real observed errors have been used, for example, by Eid et al (2004), Duvemo et al (2007), Juntunen (2006), Väisänen (2008) and simulated errors by Eid (2000), Holmström et al (2003), Holopainen & Talvitie (2006), Borders et al (2008), Islam et al (2009). One of the strengths of the case-study approach is that the observed errors are realistic and can be used as such.…”
Section: Analysing the Uncertaintymentioning
confidence: 99%
“…Real observed errors have been used, for example, by Eid et al (2004), Duvemo et al (2007), Juntunen (2006), Väisänen (2008) and simulated errors by Eid (2000), Holmström et al (2003), Holopainen & Talvitie (2006), Borders et al (2008), Islam et al (2009). One of the strengths of the case-study approach is that the observed errors are realistic and can be used as such.…”
Section: Analysing the Uncertaintymentioning
confidence: 99%
“…Most of the applications of CPL in forestry have dealt with defining the expected losses from a given data acquisition method, such as sampling-based forest inventory, traditional visual forest inventory, photo interpretation-based forest inventory, and ALS-based forest inventory (Holmström et al 2003;Eid et al 2004;Mäkinen et al 2010;Borders et al 2010). In some of the analyses, also other sources of error, such as error in the estimation of diameter distributions has been included (Bergseng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, analysis has been carried out by assuming that the utility of the decision maker only consists of the net present value (NPV) of the decision without any area-level constraints, such as even-flow or end inventory constraints. The time horizon has varied from 10 years (Holmström et al 2003) to 100 years (Eid et al 2004) and the interest rate from 2% to 4%. The calculations have been carried out with local planning systems, with either stand-level or single-tree level growth models.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is measured using simple tools, such as calliper and measuring tape. As these conventional field measurement techniques are expensive and labor-intensive [10,11], more cost-effective, automated techniques are needed. Even though the DBH is currently the most important attribute measured in ground surveys, it would be beneficial to measure the stem curve, or at least a part of it, as the stem curve actually defines the 3D geometry of the tree trunk.…”
Section: Introductionmentioning
confidence: 99%